Problematics of Qibla Direction Determination in Sei Lepan Brandan District, Langkat Regency (Analysis of MUI Fatwa No. 5 of 2010 on the Amendment of MUI Fatwa No. 3 of 2010) - Annisa Mawarni; Dhiauddin Tanjung (Dinasti Research, 2024)
Qibla direction has always been a special concern of the MUI Fatwa Commission. With this paper, it is intended to find out something that has been behind the problem of determining the Qibla direction with the issuance of the Indonesian Ulema Council Fatwa No. 5 of 2010 on the Amendment of the Indonesian Ulema Council Fatwa No. 3 of 2010. This research uses qualitative field research (Field Research) and library research (Library Research), in an analytical descriptive method. The results of the study inform that a change in the fatwa of the Indonesian Ulema Council that has been related to the Qibla position needs to be addressed reasonably. A change that occurs only in a third dictum is that changes the position of the West to the Northwest which is the Qibla of Indonesian Muslims. The first fatwa number 03/2010 only used a fiqh approach, while the next fatwa number 05/2010 used a fiqh approach, astronomy science, and falak science. In addition, determining the Qibla position is not difficult if it is carried out with an expert, even anyone can do it even in a simple way, namely Rashdul Qiblah. Therefore, calculating the Qibla position which is essentially a calculation that aims to determine the position of the Kaaba of Mecca from a position on the surface of the earth today which then every person who has performed prayers, either with a condition that is standing, ruku', or prostration which is always in a position towards the ka'bah.